Signatures of adaptation at key insecticide resistance loci in Anopheles gambiae in Southern Ghana revealed by reduced-coverage WGS - Tristan P. W. Dennis; John Essandoh; Barbara K. Mable; Mafalda S. Viana; Alexander E. Yawson; David. Weetman (Scientific Reports, 2024)
Abstract Resistance to insecticides and adaptation to a diverse range of environments present challenges to Anopheles gambiae s.l. mosquito control efforts in sub-Saharan Africa. Whole-genome-sequencing is often employed for identifying the genomic basis underlying adaptation in Anopheles, but remains expensive for large-scale surveys. Reduced coverage whole-genome-sequencing can identify regions of the genome involved in adaptation at a lower cost, but is currently untested in Anopheles mosquitoes. Here, we use reduced coverage WGS to investigate population genetic structure and identify signatures of local adaptation in Anopheles mosquitoes across southern Ghana. In contrast to previous analyses, we find no structuring by ecoregion, with Anopheles coluzzii and Anopheles gambiae populations largely displaying the hallmarks of large, unstructured populations. However, we find signatures of selection at insecticide resistance loci that appear ubiquitous across ecoregions in An. coluzzii, and strongest in forest ecoregions in An. gambiae. Our study highlights resistance candidate genes in this region, and validates reduced coverage WGS, potentially to very low coverage levels, for population genomics and exploratory surveys for adaptation in Anopheles taxa.